2020
DOI: 10.1177/0898264320953693
|View full text |Cite
|
Sign up to set email alerts
|

Dual Trajectories of Social Isolation and Dementia in Older Adults: A Population-Based Longitudinal Study

Abstract: Objectives: To identify the interrelations between the trajectories of social isolation and dementia in older adults. Methods: Data came from the National Health and Aging Trends Study 2011–2018 surveys. Group-based dual trajectory modeling was used to examine trajectories and their interrelations. Results: Four trajectories of social isolation—rarely isolated (62.2%), steady increase (13.5%), steady decrease (7.4%), and persistently isolated (16.9%) and dementia risk—persistently low risk (80.4%), increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
(80 reference statements)
1
16
2
Order By: Relevance
“…In addition, the use of social supports to reduce cognitive decline and depression should also be considered. Reducing social isolation has been shown to potentially delay the onset of dementia ( Xiang et al, 2021 ). Positive social support was shown to reduce the risk of dementia whereas negative support increased the risk among persons aged 50 years and over ( Khondoker et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of social supports to reduce cognitive decline and depression should also be considered. Reducing social isolation has been shown to potentially delay the onset of dementia ( Xiang et al, 2021 ). Positive social support was shown to reduce the risk of dementia whereas negative support increased the risk among persons aged 50 years and over ( Khondoker et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…More frequent contact will bring higher cognitive reserves, while higher cognitive capabilities can prevent dementia that may occur later [ 28 ]. Pathways associated with these connections include inflammatory responses in the brain, behavioral or neural plasticity, and the occupation of cognitive resources available for creative adaptations [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is a function which has been termed ‘pattern separation’, and has been established at a single-cell level in the rodent hippocampus (Gilbert et al, 2001; Leutgeb et al, 2007; Leutgeb et al, 2004) and neuroimaging in humans (Baker et al, 2016; Bakker et al, 2008; Berron et al, 2016; McHugh et al, 2007). An emerging view is that pattern separation is a key function altered in Alzheimer’s disease (AD) (Ally et al, 2013; Parizkova et al, 2020; Wesnes et al, 2014), while AD has analogously been linked with social isolation (Marioni et al, 2015; Penninkilampi et al, 2018; Shen et al, 2021; Xiang et al, 2021). For example, in a mouse model of AD, the investigators reported reduced Aβ synaptotoxicity in the hippocampus (Li et al, 2013), and reduced cognitive impairment (Jankowsky et al, 2005) with environmental enrichment ⍰ an important source of which in humans is regular social contact.…”
Section: Discussionmentioning
confidence: 99%